Deciphering the anticancer potential of Lannea coromandelica targeting apoptosis signal-regulatory kinase 1 via advanced computational biology approaches (Dhaka University Journal of Biological Sciences, 2025)
Colorectal cancer (CRC) is one of the leading causes of cancer-related mortality globally. The rising expenses, significant side effects, and increasing resistance to traditional CRC treatments suggest the critical need for new and more effective therapeutic options. This study explored the anticancer potential of Lannea coromandelica  (Houtt.) Merr. phytocompounds targeting the promising apoptosis signal-regulatory kinase 1 (ASK1) protein using computational biology approaches including molecular docking, ADMET analysis, molecular dynamics (MD) simulation, and MM/GBSA calculations. Virtual screening of the 17 phytoconstituents identified two lead compounds: ellagic acid and physcion, with binding affinities of -9.6 kcal/mol and -9.3 kcal/mol, respectively. ADMET analysis revealed favorable pharmacokinetic, pharmacodynamic, and toxicity profiles for the lead compounds. MD simulations supported the stability and compactness of the two leads in comparison to the control drug erbitux for 200 ns. The lead compounds displayed fewer rotatable bonds compared to Erbitux, resulting in lower torsional flexibility and greater stability during the simulations. PCA-based essential dynamics analysis demonstrated highly similar global motions in phase space for both lead compounds and erbitux, indicating comparable dynamic properties. Free binding energy calculations identified ellagic acid (-69.20 kcal/mol) as the superior lead compound over physcion (-65.68 kcal/mol). These results may open new avenues for the development of novel drug candidates targeting colorectal cancer.Dhaka Univ. J. Biol. Sci. 34(1): 1-23, 2025 (January)